Crowdsourcing : one step beyond - Lebraty, Jean-Fabrice; Lobre-Lebraty, Katia (London : ISTE ; Hoboken, NJ : Wiley, 2013)
Crowdsourcing is a relatively recent phenomenon t hat only appeared in 2006, but it continues to grow and diversify (crowdfunding, crowdcontrol, etc.). This book aims to review this concept and show how it leads to the creation of value and new business opportunities.
4.8.4.The future -- 4.9.Crowdcuration -- 4.9.1.What is it? -- 4.9.2.An illustrative example -- 4.9.3.Why it works -- 4.9.4.Limitations -- 4.9.5.The future -- 4.10.Crowdcare -- 4.10.1.What is it? -- 4.10.2.An illustrative example -- 4.10.3.Why it works -- 4.10.4.Limitations -- 4.10.5.The future -- ch. 5 The Dangers of Crowdsourcing -- ch. 6 The Future of Crowdsourcing.
Includes bibliographical references and index.
Print version record.
Keywords: Human computation; Human-computer interaction; COMPUTERS -- Computer Literacy; COMPUTERS -- Computer Science; COMPUTERS -- Data Processing; COMPUTERS -- Hardware -- General; COMPUTERS -- Information Technology; COMPUTERS -- Machine Theory; COMPUTERS -- Reference; Human computation; Human-computer interaction; Electronic books